Forests and climate change after Cancun an Asia-Pacific perspective. (RECOFTC, 2011)
The United Nations climate change talks in Cancun changed the shape of REDD+ negotiations and global forest policies. What effect will the decisions from the talks have on forests and forest users in Asia and the Pacific? Eleven climate change and forestry experts gathered to reflect on these issues, and this booklet summarizes their responses to 12 key questions.